Effect of Xenon Ion Irradiation on the Raman Spectra of BaFBr Crystals - Kenbayev, D.K.; Dauletbekova, A.K.; Karipbayev, Z.T. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2023)
Effect of Xenon Ion Irradiation on the Raman Spectra of BaFBr Crystals